Evaluation of Brushed Stainless Steel 430 Inventory Control Using The EOQ Model at PT. X - Tri Ananda Putri; Hery Irwan (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Raw material inventory control is essential for maintaining production continuity and improving cost efficiency in manufacturing companies. This study analyzes the optimization of stainless steel 430 brushed inventory at PT X using the Economic Order Quantity (EOQ) method. A descriptive quantitative approach with a case study design was employed. The analysis used annual demand, ordering cost, holding cost, lead time, and the company’s current ordering policy. The annual demand was 12,000 units, with an ordering cost of IDR 350,000 per order and a holding cost of IDR 25,000 per unit per year. Under the company’s existing policy of ordering 1,000 units per order, the total inventory cost reached IDR 16,700,000 annually. The EOQ analysis determined an optimal order quantity of 580 units, reducing the total inventory cost to IDR 14,491,379 and generating annual cost savings of IDR 2,208,621 (13.23%). The reorder point was calculated at 280 units based on an average daily demand of 40 units and a lead time of seven days. These findings indicate that the EOQ model provides a more efficient basis for inventory ordering decisions at PT X under deterministic assumptions, including constant demand, fixed lead time, and stable ordering and holding costs. However, the results are limited to deterministic inventory conditions and may not be directly applicable to environments with demand or lead-time uncertainty.